Differential functioning of mini-mental test items according to disease - G. Prieto; A.R. Delgado; M.V. Perea; V. Ladera (Neurología (English Edition), 2011)
Introduction: Comparing the height of males and females would be impossible if the measuring device did not have the same properties for both populations. In a similar way, the cognitive level of diverse groups of patients should not be compared if the test has different measurement properties for these groups. Lack of Differential Item Functioning (DIF) is a condition for measurement invariance between populations. Material and methods: The most internationally used screening test for dementia, the MMSE (or Mini-mental State Examination), has been analysed using an advanced psychometric technique, the Rasch Model. The objective was to determine the invariance of mini-mental measurements from diverse groups: Parkinson's disease patients, Alzheimer's type dementia and normal subjects. The hypothesis was that the scores would not show DIF against any of these groups. The total sample was composed of 400 subjects. Results: Significant differences between groups were found. However, the quantitative comparison only makes sense if no evidence against measurement invariance was found: given the kind of items showing DIF against Parkinson's disease patients, the MMSE seems to underestimate the cognitive level of these patients. Conclusions: Despite the extended use of this test, 11 items out of 30 show DIF and consequently score comparisons between groups are not justified. Resumen: Introducción: Sería imposible comparar la estatura de los varones y las mujeres si el metro no tuviese las mismas propiedades en ambas poblaciones. De forma similar, no se debería comparar el deterioro cognitivo de sujetos con distintas patologías si el test empleado no tuviese las mismas propiedades métricas en los grupos analizados. La ausencia de funcionamiento diferencial de los ítems (DIF) es una condición de la invarianza métrica entre poblaciones. Material y métodos: Este artículo analiza el test de cribado de la demencia más utilizado internacionalmente, el Mini-mental State Examination (MMSE), mediante un modelo psicométrico avanzado, el modelo de Rasch, con el objetivo de poner a prueba la invarianza de las medidas obtenidas en distintos grupos: pacientes con enfermedad de Parkinson, pacientes con demencia tipo Alzheimer y sujetos normales. Para ello, se ha contrastado la hipótesis de que el MMSE no muestra DIF contra ninguno de estos grupos en una muestra total de 400 sujetos. Resultados: Los resultados del análisis indican que existen diferencias significativas entre los grupos; sin embargo, la comparación cuantitativa sólo tiene sentido si no existe evidencia en contra de la invarianza métrica: dado el tipo de ítems que muestran DIF contra el grupo de pacientes con enfermedad de Parkinson, cabe pensar que el MMSE podría estar sobreestimando el nivel de deterioro cognitivo de estos pacientes. Conclusiones: Pese a lo extendido del uso del MMSE, el funcionamiento de 11 de sus 30 ítems no es igual para los distintos grupos por lo que la comparación de las puntuaciones no estaría justificada. Keywords: Screening test, Mini-mental State Examination, Testing, DIF, Parkinson's disease, Alzheimer's type dementia, Palabras clave: Prueba de cribado, Test Mini-mental, Psicometría, Funcionamiento diferencial de los ítems, Enfermedad de Parkinson, Demencia tipo Alzheimer